Study on Motivation Factors and their Affectiveness among the Students of Anatomy - Motasim Billah, Sultan Zeb, Sarah Yunus, Shehla Aman, Hafeez Baloch, Abdul Rashid Baloch (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: The learning environment influences students’ motivation, which is a critical factor of academic achievement. A variety of essential elements, including motivation, can influence student success in anatomy lessons. The present study aimed to assess various motivational factors and their effectiveness among anatomy students. Materials and Methods: This questionnaire based cross-sectional study was conducted on 140 students of anatomy in Faculty of Medicine, Gajju Khan Medical College Swabi and Gomal Medical College DI Khan. The motivation factors of anatomy students, various types of motivations, degree of motivation assessment, and improving the motivation by various parameters during their studies were assessed. SPSS version 27 was used for data analysis. Results: Of the total 140 anatomy students, there were 78 (55.7%) male and 62 (44.3%) female. The overall mean age was 22.52±4.68 years with an age range 18 years to 26 years. The overall response rate of the students was 90% (n=126). The distribution of students based on their motivational degree were as follows: 2 (1.4%) <20, 2 (1.4%) 20-40, 18 (12.9%) 40-60, 34 (24.3%) 60-80, and 84 (60%) 80-100. Male students were predominant than females. The motivation degree was 81.67% with no statistical significance between genders. Conclusion: The present study revealed that teachers may definitely target motivation as the most significant aspect to promote learning. A greater knowledge of the drivers and markers of motivation should help enhance medical student teaching to some extent. Keywords: Motivations, Anatomy students, improving learning